'Science and consciousness' of the past. A European team experience between shared research and teaching. The «Gruppo interuniversitario per la storia dell’Europa mediterranea» (GISEM) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
Tracing the long history of the Gruppo interuniversitario per la storia dell’Europa mediterranea, this contribution highlights the themes and research proposals developed over decades by scholars who, in different forms, have stimulated its initiatives. It is an opportunity to offer a re-reading of a crucial period for Italian scholarship, in the intense exchange with international medieval studies.
Keywords: GISEM; Middle Ages; History of Historiography; Italian Medieval Studies